Survey of library resources and services of land transport-related agencies in the Philippines with implications for the creation of Land Transportation Information Network (LATIN) - Opinaldo, Elsie Inosanto 1952-
As for the proposed establishment of Land Transportation Information Network, 69.23 percent expressed their willingness to join. The National Center for Transportation Studies (NCTS) library and information center was cited by the respondents as the most likely focal point for networking.